THE OPTIMIZING THE PERFORMANCE OF SATRESCRIME IN INVESTIGATIONS TO DISCLOSE THE CRIME OF CURRENCY AT THE PEMALANG POLRES - JIRZY CHAERUL FUADY (Police Studies Review, 2022)
The research in this thesis was motivated by the increasing number of motor vehicle thefts in the Pemalang Police District, but not accompanied by the resolution of cases. The research in this thesis aims to: (1) describe how the performance of the Satreskrim Polres Pemalang in uncovering the crime of theft (2) To find out what efforts are being made by the Satreskrim Polres Pemalang to optimize the performance of members in uncovering the crime of theft (3) to find out What are the factors that influence the performance of the Criminal Investigation Unit of the Pemalang Police in uncovering the crime of theft. In this study the authors used a qualitative approach with field research methods. Data collection techniques were carried out through interviews, observation and document studies. The theory used is the theory of management theory, the theory of SWOT analysis of the concept of management of criminal investigations based on the National Police Chief Regulation No. 6 of 2019. From the research results obtained data, namely: there are still many Satreskrim personnel who have not attended detective vocational education, the number of personnel is still lacking if compared to the personnel list. The handling of motor vehicle theft by the Criminal Investigation Unit of the Pemalang Police is guided by Perkap No. 6 of 2019 concerning the management of investigations but in its implementation it has not been carried out optimally so that it affects the performance of personnel. The conclusion is based on the results of the author's research that the performance of Satreskrim members is influenced by factors that influence both internally and externally. The advice given by the author based on the research that has been done is to submit recommendations to the leadership regarding the addition of the Criminal Investigation Unit personnel and recommending the detective personnel to take part in research development and vocational education, as well as submissions related to the problem of adding infrastructure and budgets to support the handling of motor vehicle theft. .